PENINGKATAN PENGETAHUAN DAN SIKAP IBU PRAKONSEPSI MELALUI EDUKASI SERIBU HARI PERTAMA KEHIDUPAN: STUDI KUASI-EKSPERIMENTAL Enhancing Knowledge and Attitude of Preconception Mother through the First Thousand Days of Life Education: a Quasi-Experimental Study - Betty Yosephin Simanjuntak; Anang Wahyudi (Media Gizi Indonesia, 2021)
Stunting is one of nutritional problem in children which the manifestation started since preconception period. Sensitive intervention is a program outside the health sector that can accelerate the improvement of nutrition, especially stunting. The purpose of this study was to increase the knowledge and attitudes of the preconception period of women regarding the fi rst 1000 days of life in order to prevent stunting. This research was a quasi-experimental study with two intervention groups. The sample was registered women, consisted of 60 women who were given education on 1000 days of life using leafl et media and 60 women using pocket book. Education was carried out by offi cers at 6 Religious Aff airs Offi ce. Women knowledge in leafl et group showed no signifi cant diff erences before and after education, especially in topics of chronic energy defi ciency (p = 0.791), anemia (p = 0.503), early breastfeeding initiation (p = 0.581), exclusive breastfeeding (p = 0.832), complementary feeding (p = 1.000), and stunting in children (p = 0.327). Among pocket book group, the increament of knowledge was better compared to leafl et group, especially in the topic of anemia (p <0.001), early breastfeeding initiation (p = 0.002), exclusive breastfeeding (p = 0.021), and stunting in children (p = 0.05). Meanwhile, the increase in attitude for all educational materials using pocket books increased with p value <0.05. Conclusion of this study was the increase in knowledge and attitudes of preconception is better in the pocket book group.